Group dynamics and creativity: a research with young adults in Reggio Emilia, Italy - Komarova, Sofya; Ndungu, Frashia; Gavazzoli, Alessia; Mineo, Roberta (Creativity Studies, 2023)
Modern society demands innovativeness and creativity. Few studies have examined group dynamics’ influence on individuals’ creativity. This study explores creativity in group settings and how the gender of participants influences group dynamics and the creative process by observing specific behaviors, including social interaction and play, creative action, and creative thinking. In groups of three, thirty participants (20–25 years) were asked to create mosaics representing a “learning community” using Lego DOTS. Relationships between group dynamics and creativity, creative thinking and creative action, gender of participants and their orientation to creativity and group dynamics were explored. Results showed negative relationships between group processes, creative thinking, and creative actions: the more intense the group dynamics were, the less the creativity. Surprisingly, female participants were more oriented to the creative task; male participants were more oriented to group dynamics. Further investigation of the relationship between creativity and cultural stereotypes on gender roles is needed.